Fistule œsotrachéale compliquant un lymphome non hodgkinien B médiastinal primitif: à propos d'un cas - Benmoussa, Amine (Pan Afr Med J, 2019)
Primary mediastinal non-Hodgkin's lymphoma(PMNHL) is a rare cancer. Exceptionally, it can be complicated by tracheœsophageal fistulas, directly connecting the esophagus and the trachea and secondary to esophageal tumor or chemotherapy (hence the interest of our case). We report the case of a 24-year old Moroccan female patient, treated for primary mediastinal large B cell NHL revealed by dyspnœa associated with dysphagia and alteration of general condition. The patient underwent chemotherapy but her health condition worsened after a second treatment due to the occurrence of recurrent pulmonary infections associated with cough during meals making swallowing impossible. Esogastroduodenal fibroscopy was performed which confirmed the diagnosis of tracheœsophageal fistula. Outcome was marked by patient's death despite endoscopic stent placement and a good response to chemotherapy. Early discovery of tracheœsophageal fistula in patients with PMNHL is essential because it enables the implementation of an appropriate treatment.